Community Composition of Dung Beetle and Population Dynamics of Tiniocellus spinipes in a Scrub Jungle Ecosystem - A, Anitha Rani.; Sanjayan, K.P. (Asian Journal of Biological and Life Sciences, 2013)
The community composition of dung beetles inhibiting the scrub jungle ecosystem was recorded by sampling beetles associated with dung pads. The survey period of two years yield 62159 individuals comprising of 33 dung beetle species belonging to the subfamilies Scarabaeinae, Coprinae and Aphodiinae. Scarabaeinae were found to be dominant in terms of species richness and abundance. Aphodius conspurcatus, Aphodius prodromus and Tiniocellus spinipes were the most dominant species. Further, the population dynamics of T.spinipes in relation to the temporal changes in the abiotic factors are also discussed as they appear to render the maximum ecological services.